Seed Germination Behavior in Garcinia imberti Bourd - Anil Kumar, C.; Prajith, T. M.; Jothish, P. S.; Chitra, C. R.; Asharf, A. (Indian Forester, 2016)
Garcinia imberti is an endemic tree of the southern Western Ghats endangered due to dwindling population and restricted distribution. At natural conditions, seeds poorly germinate and are also prone to high rate of predation. This study was carried out to investigate germination responses of both immature and mature Garcinia imberti seeds and their parts. Seeds were cut in to different parts with proximal section (PS), distal section (DS), proximal end chipped off (PEC), proximal and distal ends chipped off (PDEC) before being experimented with decoated seeds (DS) against raw seeds as control (C). The results showed significant increase of germination percentage in both immature and mature decoated seeds. Data on germination speed, seed vigour index and seedling length also favoured seed decoating treatment. The present study provided cues on seed coat imposed dormancy and survivability of sliced seeds.